Integrative taxonomy of the genus Proechimys (Rodentia: Echimyidae) from Western Amazon - Dalapicolla, Jeronymo (2019)
Proechimys is a genus of the family Echimyidae with wide distribution in the Neotropical region. Although it is abundant and widely distributed, this genus is little studied and has its taxonomy and systematics little solved. This lack of knowledge impairs studies in other areas, especially in ecology, since the species are externally similar, becoming the identification in the field and museums more difficult. There are few published studies with morphological and genetic variation, and on systematics of the genus Proechimys. The aim of this Thesis was to propose a phylogeny based on genomic data and to delimit the species of the genus, also using other dataset such as the morphometric, to better understand the diversification and evolution of Proechimys, especially in the Western Amazon. During the Ph.D. project, I identified in morphotypes and geo- referenced the localities of 3,104 Proechimys specimens in 18 museums and collections in Brazil, the USA and England, and evaluated the morphological variation from 22 quantitative characters in 1,503 specimens, and 58 qualitative characters of skull and skin in 315 specimens. In this thesis I will present the morphometric results of 479 adult specimens. The remaining morphometric and morphological data are still being studied for future publications. In addition, I sequenced part of the genome of 278 specimens using the ddRAD-seq technique to evaluate the genetic variation. Chapter 1 is a general introduction in which I presented the taxonomic history of the genus, the current knowledge on the evolutionary history of Proechimys, and remarks on the landscape evolution in Western Amazon. In addition, I discussed on species concepts and Integrative Taxonomy, themes that were addressed in this thesis. In Chapter 2, I proposed a genomic phylogeny based on genomic data, identified the clades and tested whether they could be considered different species based on the multispecies coalescent model for genetic data and Brownian motion for morphometric data. The phylogenetic relationships recovered among Proechimys individuals indicated five main clades within the genus, with statistical support for the recognition of at least 28 lineages at the species level. Proechimys was not recovered as monophyletic, and 12 of the 28 lineages did not correspond to currently valid species; some of them may be new taxa, while others may be revalidations of taxa currently included in the synonymy of valid species. In Chapter 3, I estimated divergence times between the clades and tested Bayesian models of geographic range evolution to indicate ancestral areas for the clades. With these results I created a biogeographic hypothesis for the evolution of Proechimys. The genus origin was estimated in the Miocene and in the Western Amazon. I was able to associate the biogeographic history to the landscape evolution of the Amazon. Diversification within the five main clades occurred in the Pliocene and Pleistocene. In Chapter 4, I evaluated the phylogeographic pattern of three sympatric species of Proechimys from the Western Amazon: : Proechimys brevicauda, Proechimys simonsi and Proechimys steerei. The aim was to test whether these species sharing the same geographic space would also share the same patterns of genetic structure or whether there would be segregation at the microhabitat level that would lead to different phylogeographic patterns. For this I calculated the overlap and similarity among their environmental and morphological hypervolumes, and tested the importance of barriers, the geographic and environmental distance between populations in each species to explain the genetic structure. Each species showed little overlap of the morphological hypervolume, and great overlap in the environmental one. In addition, they presented different genetic structure patterns, showing that even though they are congeners species and occur in sympatry, they may respond differently to landscape evolution, and to environmental changes. In Chapter 5, I present a synthesis of the main conclusions and future perceptives about the study of genus and the implications of my 15 results for the conservation and studies on diversity patterns in the Amazon region. Thus, this Thesis increased the knowledge on factors that lead to the genetic structure of mammalian species in the Amazon, as well as on the evolutionary history of the genus Proechimys and its genetic, morphological and species diversity. These results may support future studies in ecology, conservation biology and also fauna surveys in the Neotropical region.